THE IMPACT OF CAPITAL CONCENTRATION ON THE REALIZATION OF THE ECONOMIC INTERESTS OF AGRICULTURAL ENTERPRISES (Development Service Industry Management, 2025)
The article analyses the influence of capital concentration on the realization of the economic interests of agricultural enterprises in the context of the transformation of Ukraine's agricultural market. The paper considers current trends in strengthening the positions of extensive agricultural holdings, increasing vertical and horizontal integration, and changing the role of small and medium-sized agricultural enterprises (SMEs) in the structure of agricultural production. It is determined that the concentration of capital has an ambiguous impact on the industry: on the one hand, it contributes to increasing technological capabilities, efficiency of production processes, opportunities for scaling and attracting investments; on the other hand, it is accompanied by risks of increasing monopolization, weakening market competition, reducing the share of SMEs and limiting their access to key resources, in particular land, infrastructure and financial instruments. The study systematizes the advantages and risks of capital concentration. It is shown that, despite the obvious economic benefits, high concentration can create structural imbalances that contradict the economic interests of many agricultural producers and rural areas. Special attention is paid to the analysis of the impact of capital concentration on MRAPs' strategic interests, their ability to develop, compete, integrate into export chains, and ensure the sustainable development of communities. It is proven that the concentration of capital creates both economic opportunities and systemic challenges that require balanced state policy, effective antitrust regulation, and instruments to support small- and medium-sized agricultural producers. The results obtained have practical significance for the formulation of strategic decisions at the enterprise level and for the development of state policy for the farm sector.
Keywords: concentration; capital; economic interests; risks; approach to development management